Evaluation of urea and creatinine levels in vaginal wash fluid for the diagnosis of premature rupture of membranes - Sharma, Abha; Sharma, Richa; Agarwal, Tannavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Evaluation of urea and creatinine levels in vaginal wash fluid for the diagnosis of premature rupture of membranes. Methods: The study was conducted on150 pregnant patients, 50 in each group. Confirmed PROM and unconfirmed PROM. Per speculum examination was done to look for pooling, pH tested using the Pehanon paper and vaginal wash fluid was collected. Vaginal wash fluid urea and creatinine levels were tested by a kit based on spectrophotometry. Results: The mean urea levels were 26.35 mg/dl in the study Group 1 and 3.12 mg/dl in the control group. ROC curve was plotted and the cut off value of vaginal wash fluid urea was found to be 8.55 mg/dl. The vaginal wash fluid urea levels of >8.55 mg/dl detected PROM with a sensitivity, specificity, negative and positive predictive value of 100%. The mean creatinine levels were 0.62 mg/dl in study Group 1 and 0.20 mg/dl in the control group. ROC curve was plotted and the cut off value of vaginal wash fluid creatinine was found to be 0.405 mg/dl. Vaginal wash fluid creatinine levels detected PROM with a sensitivity of 76% and specificity of 100%. The negative predictive value and positive predictive values were 80.4% and 100%. Conclusions: Urea can be used as a definite marker of PROM and creatinine can be used as a supportive marker.